Influencia de condiciones (tiempo y temperatura) del tostado de cacao en microempresas artesanales de Manabí en la calidad integral del chocolate - Loor Cedeño, Jaén Renán (2023)
This research work aims to evaluate the conditions (time and temperature) of cocoa roasting in artisanal micro-enterprises in Manabí regarding the integral quality of the chocolate. The roasting process was observed in each micro-enterprise coded by the initial of the producer's name and surname together with the visit number. After several processes, chocolate bars with 70% cocoa were obtained, which underwent physical (granulometry), chemical (percentage of cocoa butter) and sensorial. To analyze the results, basic statistics were used, applying measures of central tendency and representation of quantitative variables through a radial graph. Roasting time is between 20 and 70 minutes, with temperatures between 100ºC and 130ºC. The grain size in the chocolates was 15 to 26 microns, showing the influence of conching time and the conditions under which roasting is carried out, that is, equipment, grain humidity and temperature control tools. The cocoa butter content at temperatures between 110ºC and 130ºC was 37 to 39%, while at temperatures of 100ºC it was between 41% and 47%. Roasting temperatures above 100ºC for prolonged periods reduce the percentage of cocoa butter in the bean, thus reducing its chocolate content. At a sensorial level, the microcompany MA11 (120ºC-20min) highlighted the general attributes of artisanal chocolate, while the aromas prevailed in the chocolate from RM04 (100ºC-30min). But it was WL07 (110ºC-40min) that currently does not present any defects in its product.